The changes of Treg and Th17 cells relate to serum 25(OH)D in patients with initial-onset childhood systemic lupus erythematosus - Jiang, Li-jun; Rong, Zan-hua; Zhang, Hui-feng (Frontiers in Pediatrics, 2023)
Background T helper 17 (Th17) cells and Regulatory T cells (Treg) are known to play a crucial role in the pathogenesis of systemic lupus erythematosus (SLE). Improving the balance between Treg and Th17 cells can be a promising new therapeutic target in SLE patients. Vitamin D has a significant impact on the immune inflammatory process and the immune cells involved in this process. The purpose of this study is to investigate the relationship between Th17, Treg, cytokines and serum 25(OH)D in initial-onset childhood SLE patients. Methods A total of 82 children aged <18 with initial-onset SLE were included, as well as 60 healthy subjects during the same period at the Pediatrics Department of the Second Hospital of Hebei Medical University. The detection of serum 25(OH)D was carried out by the chemiluminescence method. Treg and Th17 cells were evaluated by using flow cytometry. Plasma interleukin (IL)-23, IL-17, IL-10, IL-6, and tumor necrosis factor alpha (TNF–α) concentrations were evaluated by enzyme-linked immunosorbent assay kit. Result The serum 25(OH)D levels in initial-onset childhood SLE patients were significantly lower than that in the healthy controls. The proportion of lupus nephritis (LN) was higher in vitamin D insufficiency group (71.4%) compared with vitamin D sufficiency group (30.3%) (P<0.05). The SLE Disease Activity Index (SLEDAI) was higher in vitamin D insufficiency group (median=14) than that in vitamin D sufficiency group (median=9) (p<0.05).The 25 (OH) D level was positively correlated with Treg ratio (r=0.337, p=0.002), and negatively correlated with Th17 cell ratio (r=-0.370, p=0.001). Serum 25(OH)D level had negative correlation with IL-23 (r= -0.589, p<0.001), IL‐17(r=-0.351, p=0.001), TNF-α (r=-0.283, p=0.01), IL-6 (r=-0.392, p<0.001) and IL‐10 (r=-0.313, p=0.004) levels. Conclusion The serum 25(OH)D levels decreased in initial-onset childhood SLE patients. There was a negative correlation between serum 25(OH)D levels and SLEDAI. The serum 25(OH)D levels in initial-onset childhood SLE patients were negatively correlated with Th17 ratio and related cytokines, while positively correlated with Treg ratio.